1998
DOI: 10.1007/s004390050786
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical study of 183 patients with conotruncal anomaly face syndrome

Abstract: To investigate molecular and clinical aspects of conotruncal anomaly face (CAF), we studied the correlation between deletion size and phenotype and the mode of inheritance in 183 conotruncal anomaly face syndrome (CAFS) patients. Hemizygosity for a region of 22ql1.2 was found in 180 (98%) of the patients with CAFS by fluorescence in situ hybridization (FISH) using the N25(D22S75) DiGeorge critical region (DGCR) probe. No hemizygosity was found in three (2%) of the patients with CAFS by FISH using nine DiGeorge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
2
9

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 26 publications
3
81
2
9
Order By: Relevance
“…1, Table 1). Variants of 3 Mb deletions have been reported previously (Matsuoka et al 1998;Saitta et al 2004;Urban et al 2006). It appears likely though that, due to lower resolution methods, some of the "common 3 Mb deletions" reported in previous studies may have included both the most common 3.1 Mb deletion as well as the type variants found in our study.…”
Section: Common Deletion Variants and Recurrent Breakpoint Regionsmentioning
confidence: 91%
“…1, Table 1). Variants of 3 Mb deletions have been reported previously (Matsuoka et al 1998;Saitta et al 2004;Urban et al 2006). It appears likely though that, due to lower resolution methods, some of the "common 3 Mb deletions" reported in previous studies may have included both the most common 3.1 Mb deletion as well as the type variants found in our study.…”
Section: Common Deletion Variants and Recurrent Breakpoint Regionsmentioning
confidence: 91%
“…1). 17 Medical records of these 34 patients were reviewed. Congenital heart diseases were diagnosed by echocardiography, cardiac catheterization and angiocardiography.…”
Section: Methodsmentioning
confidence: 99%
“…The "classic" CVMs occurring in patients with deletion 22q11 are conotruncal defects, [2][3][4][5][6][7][8][9][10] including tetralogy of Fallot (TF), pulmonary atresia with ventricular septal defect (PA-VSD), truncus arteriosus (TA) and interrupted aortic arch (IAA), but also ventricular septal defect was commonly described. However, in children with this syndrome, other types of CVM were occasionally reported, including atrial septal defect, atrioventricular canal, tricuspid atresia, transposition of the great arteries, hypoplastic left ventricle, heterotaxy, aortic coarctation, vascular rings, and other anomalies of the aortic arch.…”
mentioning
confidence: 99%
“…However, in children with this syndrome, other types of CVM were occasionally reported, including atrial septal defect, atrioventricular canal, tricuspid atresia, transposition of the great arteries, hypoplastic left ventricle, heterotaxy, aortic coarctation, vascular rings, and other anomalies of the aortic arch. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The accurate study of cardiac phenotype revealed that additional CVMs are common in children with conotruncal defects and deletion 22q11 so that distinctive patterns could be recognized in patients with this syndrome as well as were recognized in patients with other genetic syndromes. [15][16][17][18] In this report, we summarize our experience and the cardiac anatomy in children with conotruncal defects and deletion 22q11, describing the association with phenotypical findings.…”
mentioning
confidence: 99%